State Sovereignty and Humanitarian Assistance: Navigating the Tension in International Armed Conflicts - Puspoayu, Elisabeth Septin; Widagdo, Setyo; Kusumaningrum, Adi; Kurniaty, Rika (International Law Discourse in Southeast Asia, 2024)
This paper critically examines the intersection of state sovereignty and the provision of humanitarian assistance in the context of international armed conflicts, addressing a pressing and increasingly relevant issue in global legal discourse. While state sovereignty remains a cornerstone of international law, its application during armed conflict, especially regarding external humanitarian aid, raises complex questions of responsibility and intervention. Using a blend of primary and secondary legal sources, the study explores how sovereignty intersects with the state's obligations to protect and meet the needs of its citizens during conflict, in line with the theory of "responsible sovereignty." The research highlights the nuanced tension between a state's right to control its territory and its duty to ensure the welfare of its population, even in the midst of war. Despite the fundamental principle of sovereignty, states are bound by international norms to allow humanitarian assistance when their capacity to respond to crisis situations is overwhelmed, thereby preventing further human suffering. The study challenges the traditional view that external aid constitutes an infringement on sovereignty, instead arguing that the refusal of humanitarian assistance in times of need may violate international legal and moral obligations. This paper offers a novel perspective on sovereignty, proposing that in an era of global interconnectedness and humanitarian crises, responsible sovereignty should prioritize the protection of human life over rigid territorial control. The findings contribute to ongoing debates in international law, urging a rethinking of the state's role in conflict zones and the responsibility to allow external humanitarian aid in the face of dire need.